2021
DOI: 10.1007/s10098-021-02132-w
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of tobacco processing waste to biocrude oil via hydrothermal liquefaction in a multiple batch reactor

Abstract: Graphic abstract Fossil fuels are the primary energy source of almost all societies and economies, but it is finite and scarce. The use of non-renewable fossil fuels threatens earth’s environment. At the same time, waste from agricultural and industrial activities is increasing. Most of this waste is discarded or poorly managed, causing many other environmental issues. Converting waste to energy is a promising route to address these challenges. We investigated the hydrothermal liquefaction (HTL) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…On the other hand, the study of Wang et al explored the corn stalk performance of the wet torrefied sample's performance in biomass pyrolysis polygeneration, wherein the fixed-bed reactor was employed, and which had biochar as the output product. Aside from the above-mentioned, all the studies shown in Table 2 appear to have resembling analytical methods, which largely involved moisture, organic matter, and ash content, with very few exceptions [15,25,52,54,60,65,83,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Palamanit and colleagues used an agitated bed pyrolysis reactor to examine the yields and characteristics of pyrolysis products obtained from oil palm fronds, trunks, and shells.…”
Section: Pre-to Post-pyrolysis' Engagement Strategiesmentioning
confidence: 99%
“…On the other hand, the study of Wang et al explored the corn stalk performance of the wet torrefied sample's performance in biomass pyrolysis polygeneration, wherein the fixed-bed reactor was employed, and which had biochar as the output product. Aside from the above-mentioned, all the studies shown in Table 2 appear to have resembling analytical methods, which largely involved moisture, organic matter, and ash content, with very few exceptions [15,25,52,54,60,65,83,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Palamanit and colleagues used an agitated bed pyrolysis reactor to examine the yields and characteristics of pyrolysis products obtained from oil palm fronds, trunks, and shells.…”
Section: Pre-to Post-pyrolysis' Engagement Strategiesmentioning
confidence: 99%
“…The HHV of bio-oil was similar for all the types of feedstock used and it was in the range of 33–34 MJ kg −1 . The possibility of the conversion of tobacco processing waste to bio-oil through the HTL process was studied by Saengsuriwong et al 307 The reaction was performed in a batch reactor at 280–340 °C and 22 MPa. The highest yield of bio-oil (52 wt%) was obtained at 310 °C with a HHV of 31.9 MJ kg −1 for the heavy fraction of the bio-oil and 28.4 MJ kg −1 for the light fraction of the bio-oil.…”
Section: Biorefinery Based On the Thermochemical Treatment-commercial...mentioning
confidence: 99%
“…37 The portions of nicotine were N-containing compounds, which can only be from the feedstock. Nitrogen was a slightly small content in the feedstock, 13,27 but it can contribute a lot of reactions. Maillard reaction typically came from the degradation of sugars and amino acids.…”
Section: Possible Pathway For Htl Of Tobacco Residuesmentioning
confidence: 99%
“…Apart from upgrading processes such as ionic liquid pretreatment 6 and torrefaction 7 9 where some unwanted properties of biomass are addressed, it can be converted to biofuels and biochemicals using modern thermochemical platforms such as gasification, 10 pyrolyses, 11 , 12 and hydrothermal processing. 13 In Thailand and many countries, tobacco is a secondary-income-generating crop traditionally used for manufacturing cigarettes. Resulting tobacco residues, a very high moisture content type of biomass, are usually rid by landfilling or incineration, causing noxious emissions and affecting environmental wellbeing.…”
Section: Introductionmentioning
confidence: 99%